Design of Back-to-Back Converter Interface for Electric Spring in a Distribution System - Deepika, K. K.; Kumar, J. Vijaya; Pinni, Srinivasa Varma; Sura, Srinivasa Rao; Sankar, R. S. Ravi (Frontiers in Energy Research, 2022)
In a distribution system, the erratic output power of distributed generation causes fluctuations in the available power to critical loads on the demand side. A novel electric spring (ES) with back-to-back converter configuration is proposed. Besides PCC voltage regulation and power control, the proposed converter integrates the ES to the grid without compromising the DC link voltage and the quality of the grid current. It comprises an instantaneous DC link voltage control, active power control, PCC voltage control, and a hysteresis band current control. The systematic design of the parameters in the configuration is detailed. Simulations were performed in MATLAB/Simulink, and a series of comparative analyses at various control stages were demonstrated. The quality of the grid current was analyzed with PI, PR, and hysteresis band current controllers. It was established that the hysteresis band current controller gave the best performance. Similarly, the DC link voltage was efficiently regulated with the instantaneous DC link voltage controller than the conventional controller.